Impact of Head‐Down Position on Cerebral Blood Flow in Healthy Subjects: An Arterial Spin‐Labeling MR Perfusion Study - Mejdoubi, Mehdi; Pavilla, Aude; Colombani, Sylvie; Duvauferrier, Régis; Cepeda Ibarra, Yamilet; Seiller, Ian (Journal of magnetic resonance imaging, 2020)
Background A head‐down (HD) position is used in some stroke centers to maintain cerebral perfusion (CP) in stroke patients. Purpose To assess CP in healthy volunteers in the supine and HD (–15°) positions. Study Type Prospective. Population Eighteen healthy subjects of 53 (±8) years old. Field Strength/Sequence 1.5T / arterial spin‐labeling (ASL) in the supine position and after 4 minutes of HD position. Assessment Regions of interest from reconstructed cerebral blood‐flow (CBF) maps: subcortical nuclear gray matter (accumbens, amygdala, caudate, hippocampus, pallidum, putamen, thalamus), cortical gray matter (cGM), and white matter (WM). We also monitored hemodynamic parameters. Statistical Tests Shapiro–Wilk test, analysis of variance (ANOVA) tests, Student's t‐tests, and Pearson correlation analysis. Results CBF was higher in women compared to men, whatever the position (mean difference of 17% in supine, and 13% in HD position). From supine to HD position, CBF was decreased in all regions (mean decrease of –7%). Simultaneously, mean arterial pressure and systolic blood pressure increased (respectively P = 0.004 and P < 0.001). Data Conclusion The CBF decrease, despite increased hemodynamic parameters, may indicate efficient cerebral autoregulation. Our results seem to reflect only early cerebral autoregulation stages but may open the way towards a more precise understanding of CP. Level of Evidence: 1 Technical Efficacy Stage: 2 J. Magn. Reson. Imaging 2020;51:218–224.